Efficacy of chemotherapy after progression with nivolumab in squamous cell carcinoma of the head and neck. Issue 3 (June 2020) - Suzuki, Shinsuke; Toyoma, Satoshi; Tomizawa, Hiroki; Yamada, Toshiki; Iikawa, Nobuko; Shiina, Kazuhiro; Saito, Hidekazu; Koizumi, Koh; Kawasaki, Yohei; Yamada, Takechiyo
Abstract: Nivolumab, a programmed death-1 (PD-1) inhibitor, has shown promising results against squamous cell carcinoma of the head and neck (SCCHN) in cases of recurrence or in a metastatic setting after platinum-based therapy. However, treatment alternatives for patients with nivolumab-refractory are limited, and a constant opinion is not provided. Recently, accumulating studies have demonstrated that chemotherapy after immune checkpoint inhibitor treatment may induce better objective responses in patients with advanced non-small cell lung cancer. However, there are few reports on the increased effect of chemotherapy after nivolumab treatment in SCCHN. Therefore, cases must be accumulated to identify patients with nivolumab-refractory SCCHN who may benefit from chemotherapy. Here, we present patients with SCCHN who exhibited a significant response to chemotherapy after nivolumab treatment.